Medication adherence and predictors men who have sex with men with HIV accessing antiretroviral therapy services di south Sumatera, Indonesia: A retrospective study - Kurrohman, Taufik; Sitorus, Rico Januar; Legiran, Legiran; Yunindyawati, Yunindyawati (International Journal of Innovative Research and Scientific Studies, 2025)
Men who have sex with men (MSM) are more likely to engage in risky sexual behaviors such as anal intercourse, oral sex, and mutual masturbation, which increase their risk of acquiring human immunodeficiency virus (HIV). Previous studies have emphasized that MSM diagnosed with HIV should initiate antiretroviral therapy (ART) promptly, with strict adherence being critical for treatment effectiveness. This study aims to identify factors associated with treatment adherence among MSM living with HIV. A retrospective cohort study was conducted involving 796 MSM with HIV who accessed health services in South Sumatra up to June 2024. The majority of participants were younger than 40 years (85.1%) and had an education level of senior high school or below (84.9%). Overall, 21.5% of patients were non-adherent to treatment, with 4.8% experiencing side effects and 13.1% presenting with opportunistic infections. Multivariate analysis indicated that treatment side effects and clinical stage were significant predictors of adherence. Treatment side effects and clinical stage play a critical role in determining adherence among MSM with HIV.